(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Postcolonial literature frequently explores themes of displacement, fractured identities, and cultural alienation, often using humour as a means of critique and survival. V.S. Naipaul’s Miguel Street exemplifies this narrative approach, depicting the lives of marginalized individuals in a post-colonial society grappling with the residual effects of colonialism. This study examines the intersection of humour, displacement, and the illusion of self in Miguel Street, highlighting how Naipaul employs satire, irony, and caricature to interrogate post-colonial identity formation. The study addresses a critical gap in post-colonial literary studies by exploring the complex relationship between humour and the psychological effects of displacement. While existing scholarship has primarily focused on the socio-political dimensions of Miguel Street, this study shifts the focus to the novel’s portrayal of self-perception and existential alienation within a post-colonial framework. The theoretical foundation for this research is drawn from post-colonial theory, particularly the works of Homi Bhabha on hybridity and mimicry, Frantz Fanon’s insights on colonial subjectivity. Methodologically, this study employs a close textual analysis of Miguel Street, focusing on narrative structure, character development, and thematic representations of humour and identity. Comparative literary analysis is also employed to position Naipaul’s work within broader post-colonial discourses. The findings reveal that humour in Miguel Street serves as both a coping mechanism and a subversive tool that challenges colonial and post-colonial power structures. The study further demonstrates that displacement in Naipaul’s narrative extends beyond physical dislocation, encompassing psychological and existential estrangement. By bridging the gap between post-colonial identity studies, this study contributes to the growing discourse on the role of narrative techniques in post-colonial literature. It further reveals the necessity of re-examining humour as a fundamental narrative device that not only reflects but actively constructs post-colonial subjectivities. The study ultimately enriches scholarly understandings of identity, displacement, and the performative aspects of selfhood in post-colonial contexts.